Intervention strategies to improve adherence to the five pillars of diabetes management among patients with type 2 diabetes mellitus: A literature review - Megawati, Putu Vera; Agustini, Ni Luh Putu Inca Buntari; Megayanti, Sri Dewi; Sari, Ni Made Candr Citra (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Diabetes mellitus is a metabolic disease that is a global problem, with the number of sufferers increasing annually. Adherence to the five pillars of diabetes management is the cornerstone of preventing and reducing morbidity and mortality from diabetes. Purpose: To analyze how to improve adherence in type 2 diabetes patients in implementing the five pillars of diabetes management. Method: The research method used a literature review approach to map and identify interventions for implementing the 5 pillars of diabetes management. Results: The study found 20 articles describing interventions for people with diabetes mellitus through educational and informational delivery mechanisms. The types of interventions included: mobile phone application interventions, physical exercise interventions, audiovisual interventions, flipchart interventions, and peer leader interventions. Conclusion: Five types of interventions improve adherence in patients with type II diabetes mellitus to implementing the 5 pillars of diabetes management.